Edukasi Tentang Pemahaman Kekerasan Seksual Pada Anak – Anak di Desa Landbaw - Chindie Mutiara Dihan; M. Andreansyah Putra Anwar; Ulil Albab; Maya Syafira; Ahmad Zaenuri (Lembaga Pengembangan Kinerja Dosen, 2024)
In various regions of Indonesia, violence against children has become one of the most concerning issues. The high amount of media coverage regarding cases of sexual violence against children serves as evidence that many cases are still occurring. The lack of education about sexuality for children from a young age is one of the triggering factors for the increase in incidents of sexual harassment. Sex education for children is still considered a taboo by society, especially among parents. The lack of education causes children to be unaware of the crimes of sexual violence that may occur around them. Educational activities in the form of sexual education as part of community service programs are one of the efforts to prevent sexual violence against children. The purpose of this activity is for students to understand and recognize the importance of preventing sexual violence, so that they can take appropriate action if they encounter a dangerous situation.